Labour in Contemporary Capitalism What Next? - Huws, Ursula (Dynamics of Virtual Work, 2019)
In this long-awaited book, Ursula Huws brings together the results of decades of prescient research on labour market transformation to provide an authoritative overview of the impacts of technological, economic, social and political change on working life in the 21stcentury. Placing current upheavals in global labour markets firmly in their historical context, she debunks myths about the impacts of artificial intelligence on labour, pointing to the processes whereby new employment is created, as well as old jobs destroyed, while never underestimating the contradictory impacts of digitalisation on work organisation, resistance, adaption and innovation. This book is underpinned by a clear conceptual framework, that analyses the dynamics of the restructuring of capitalism and labour, taking full account of unpaid social reproductive work, and integrating a feminist analysis whilst also pointing to new forms of commodification that will shape the future. Labour in Contemporary Capitalism will be an invaluable resource and point of reference for students and scholars studying the sociology of labour, economic structures, technology, and globalisation. .